2022
DOI: 10.1002/cptc.202100272
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic H2 Evolution by Hexaniobate Nanosheets Grafted with Copper Nanoclusters

Abstract: Hexaniobate nanosheets (K4−xHxNb6O17) were combined with Cu2+ ions by grafting, a green one‐step methodology. The resulted nanocomposite exhibits high surface area with most of the Cu2+ ions strongly connected to the hexaniobate layers as amorphous nanoclusters. Photocatalytic experiments evidence that the Cu‐grafted hexaniobate can act as an efficient photocatalyst for H2 evolution. The best performance for the Cu‐grafted hexaniobate was reached when the Cu concentration was 0.5 wt% (1.62±0.10 mmo g−1 h−1), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…As described for iron, the loss or gain of Cu 2+ signals during catalysis can be used as a marker for low-valent or high-valent Cu ions. 78–80 For example, when comparing the EPR signals of CuO/SiO 2 , 11 Cu/Zn–Al, 79 Cu/K 4− x H x Nb 6 O 17 81 and CuO/TiO 2 82 before and during the catalytic measurements, a loss in EPR intensity could be attributed to reduction of Cu 2+ to Cu + . Moreover, it was shown that addition of an iridium complex (as a photosensitizer) or glycerol (as a sacrificial agent) suppressed reduction of Cu 2+ .…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%
“…As described for iron, the loss or gain of Cu 2+ signals during catalysis can be used as a marker for low-valent or high-valent Cu ions. 78–80 For example, when comparing the EPR signals of CuO/SiO 2 , 11 Cu/Zn–Al, 79 Cu/K 4− x H x Nb 6 O 17 81 and CuO/TiO 2 82 before and during the catalytic measurements, a loss in EPR intensity could be attributed to reduction of Cu 2+ to Cu + . Moreover, it was shown that addition of an iridium complex (as a photosensitizer) or glycerol (as a sacrificial agent) suppressed reduction of Cu 2+ .…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%
“…The combination of metal nanoparticles with metal oxides to produce high-performance photocatalysts has been largely explored in the last decades. In principle, light harvesting is carried out by the band gap excitation of the semiconductor phase, whereas the metallic nanoparticles work first as electron acceptors, enhancing the charge separation efficiency, and then as catalytic surfaces, promoting reduction reactions, such as hydrogen evolution. To this end, noble metals such as Pt, Au, Ag, and Pd have been employed with binary and ternary metal oxides. Pt is considered a benchmark for H 2 evolution given its high reactivity, but a lot of attention has been given to Au nanoparticles given the possible photosensitization of the semiconductor (mainly TiO 2 ) in the visible region owing to their characteristic surface plasmon resonance (SPR) absorption band. Alternatively, earth-abundant Cu 0 -based composites have also been proposed. , …”
Section: Introductionmentioning
confidence: 99%